Ultra-small self-discharge and stable lithium-sulfur batteries achieved by synergetic effects of multicomponent sandwich-type composite interlayer. (August 2018) - Wang, Lehong; He, Yan-Bing; Shen, Lu; Lei, Danni; Ma, Jiaming; Ye, Heng; Shi, Kai; Li, Baohua; Kang, Feiyu
Abstract: The severe lithium polysulfide (LiPS) shuttling and self-discharge behavior of lithium-sulfur (Li-S) batteries remarkably hinder their practical application. The construction of interlayer is an effective strategy to obstruct the diffusion of LiPS. However, the simplex physical block or chemical absorption of monotonous interlayer is difficult to reuse sulfur species, reduce impedance and restrain self-discharge of the Li-S battery simultaneously. In this study, a multicomponent sandwich-type interlayer was integrated by vanadium disulfide and carbon nanotubes composite (VS2 /CNT), carbon nanofibers (CNF) substrate and graphene coating layer. The VS2 /CNT presented strong affinity towards LiPS and effectively restrained the self-discharge of Li-S batteries. The CNF substrate as supporting framework increased the wettability of electrolyte and reduced the diffusion impedance of lithium ion. The graphene coating layer acting as the second collector effectively recovered the inactivated sulfur species. The multiple components of VS2 /CNT adsorbent, CNF substrate and graphene coating layer exhibited favorable synergetic effects to suppress the LiPS shuttling and self-discharge of Li-S batteries. Besides, this interlayer endowed Li-S batteries with boosted redox kinetics and outstanding rate performance. The specific capacities at 0.1, 1 and 10 C were 1525, 834 and 621 mAh g −1, respectively. More importantly, the Li-S batteries with this multicomponent interlayer performed a high residual capacity of 605 mAh g −1 after 1145 cycles at 1 C. Even at a high sulfur loading of 5.6 mg cm −2, the cell still had high capacity of 1150 mAh g −1 and 750 mAh g −1 at 0.1 C and 0.3 C, respectively. The synergetic effects of multicomponent sandwich-type composite interlayer provided a new strategy for ultra-small self-discharge and stable of Li-S batteries. Graphical abstract: fx1 Highlights: VS2 /CNT is supported on CNF framework and covered with graphene to form an interlayer. The VS2 /CNT presents strong affinity towards lithium polysulfide. The CNF, VS2 /CNT and graphene show highly synergetic effects. The interlayer endows Li-S batteries with outstanding electrochemical performance.